Unilateral Oral Mucous Membrane Pemphigoid: Refractory Atypical Presentation Successfully Treated with Intravenous Immunoglobulins - Laureano, A (2015)
A 57-year-old male presented with a 6-month history of blisters and painful erosions on the right buccal mucosa. No skin or other mucosal involvement was seen. The findings of histopathological and direct immunofluorescence examinations were sufficient for the diagnosis of oral mucous membrane pemphigoid in the context of adequate clinical correlation. No response was seen after topical therapies and oral corticosteroids or dapsone. Intravenous immunoglobulin was started and repeated every three weeks. Complete remission was achieved after three cycles and no recurrence was seen after two years of follow-up. The authors report a rare unilateral presentation of oral mucous membrane pemphigoid on the right buccal and hard palate mucosa, without additional involvement during a period of five years. Local trauma or autoimmune factors are possible etiologic factors for this rare disorder, here with unique presentation.